The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/23874
|View full text |Cite
|
Sign up to set email alerts
|

Formative Study of Mobile Phone Use for Family Planning Among Young People in Sierra Leone: Global Systematic Survey

Abstract: Background Teenage pregnancy remains high with low contraceptive prevalence among adolescents (aged 15-19 years) in Sierra Leone. Stakeholders leverage multiple strategies to address the challenge. Mobile technology is pervasive and presents an opportunity to reach young people with critical sexual reproductive health and family planning messages. Objective The objectives of this research study are to understand how mobile health (mHealth) is used for f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The increasing penetration of mobile phones or digital media platforms are an emerging opportunity to engage young audiences in most need [39]. Mobile phones also represent the most rapid expansion as a medium for mass media messaging globally and in Sierra Leone [40].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing penetration of mobile phones or digital media platforms are an emerging opportunity to engage young audiences in most need [39]. Mobile phones also represent the most rapid expansion as a medium for mass media messaging globally and in Sierra Leone [40].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, UNFPA conducted formative research to understand how young people use mobile phones and the best strategy for reaching young people using mobile technology with SRH messages. The report showed that phone ownership and phone type increased with education and income ( 20 ). Young people, out of school, generally used basic phones and often could not read or write.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Multichannel here refers to the use of several media channels for spreading marketing and health promotion and education messages to consumers and service users, including via social media, print, mobile, television, etc. ( 20 , 21 ). The multiple channels adopted in this project were automated voice calls, SMS, radio jingles, and social media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 Youth by Youth mHealth photo verification app for self-texting was found to be feasible by Nigerian youth [ 15 ]. Text messaging was recommended to provide family planning information to adolescent and young adult women in Sierra Leone [ 16 ]. In Zambia, the Insake mobile phone app provided support to pregnant women living with HIV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%